Pengaruh Perlakuan Pupuk Cair Dari Limbah Organik Terhadap Pertumbuhan Tanaman Bunga Pacar Air (Impatiens balsamina L). - I Made, Budiasa; Aplorida Lingu Lango; I Ketut Widnyana; I Ketut Sumantra; I Gusti Ayu Diah Yuniti (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2021)
The research entitled “The effect of Liquid Fertilizer Treatment from Organic Waste on the Growth and Yield of (Impantiens balsamina L aims to determine the effect of giving organic liquid fertilizer to the growth and yield of I balsamina. This study used a Randomized Block Design (RAK) with 9 treatment which were repeated 4 times so that there were 36 experimental pots. The treatments are control (without fertilize), chemical fertilizer, POC vegetable waste, fruit waste POC, fish waste POC, seaweed POC, bio urine POC, cow rumen POC, and a mixture of all types or organic liquid fertilizer, with a dose of 20% each. The result showed that the effect of POC treatment had a signicant effect on all growth parameter and yields of I balsamina, except for the parameter of the number of flowers per plant which was not significantldi fferent. The result showed that the mixed POC treatment gave the best effect but was not significantly different from all other treatments